To what extent do investors in a financial market anchor their judgments? Evidence from the Hong Kong horserace betting market - Johnnie E.V. Johnson; Shuang Liu; Adi Schnytzer (Bar-Ilan University, Department of Economics, 2011)
This paper explores the use of the anchoring and adjustment heuristic by decision makers in a financial market; in particular, the degree to which horserace bettors anchor their probability judgments on the advantage afforded by a horse's barrier-position. The results suggest that under certain conditions bettors anchor on barrier-position information revealed at previous race meetings, but not on the most recent race outcomes. In fact, bettors appear to use the most recent race outcomes appropriately when forming probability estimates; but only when the results are in line with their mental model of barrier-position advantage. Bettors with varying levels of expertise are shown to be subject to anchoring, although greater expertise is generally associated with less anchoring. The paper concludes that the manner and degree of anchoring in real world environ.
Keywords: 330; Pferdesport; Glücksspiel; Entscheidung; Hongkong